Efficacy and Safety of Glecaprevir/Pibrentasvir in Chronic Hepatitis C Patients: Real-World Data - Muhammet Rıdvan Tayşi; Yakup Gezer (Mediterranean Journal of Infection, Microbes and Antimicrobials, 2025)
Introduction: Glecaprevir/pibrentasvir (G/P) is a pan-genotypic direct-acting antiviral therapy approved for use in adults with chronic hepatitis C virus (HCV) infection. This study aimed to assess the real-world efficacy and safety profile of G/P in individuals with chronic HCV. Materials and Methods: The analysis included patients over 18 years with detectable HCV-RNA who began G/P treatment for chronic HCV between January 1, 2021, and March 1, 2024. The primary outcome measure was sustained virologic response (SVR), defined as undetectable HCV-RNA 12 weeks after therapy completion. Safety and tolerability of the regimen were also evaluated. Results: G/P was administered to 191 patients, of whom 85.5% were male. Among them, 124 patients (64.9%) reported intravenous drug use. The most frequently identified genotype was GT 3 (57.1%). At 12 weeks post-treatment, 105 patients returned for follow-up, and all achieved SVR12. Adverse events occurred in 12 patients (6.3%). One patient discontinued treatment at week 4 due to pruritus and rash. Conclusion: G/P demonstrates high effectiveness, good tolerability, and a favorable safety profile as a pan-genotypic therapeutic option for chronic HCV infection.